Pembuatan Kompor Portebel Menggunakan Spritus/Alkohol Desa Bagelen - Rajiman; Any Nurhasanah; Ronny Hasudungan Purba; Titis Lukita Sari (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Village community empowerment is a conscious effort from government officials both at the village and district levels, especially towards a potential that exists in the village as a form of assets/wealth owned by the village. This research is about community service in making portable stoves. The method used is descriptive qualitative research. This research was conducted in Bagelan Village, Gedong Tataan District, Pesawaran Regency. Participants in this activity are residents of Bagelan Village. The purpose of this study is to reveal knowledge about portable suitcases, and as a form of concern for areas that still lack funds or sales of LPG gas. From this research, this portable stove is very useful because in terms of its simple use and economical cost, the Pertebel stove can also overcome the scarcity of other fuels such as 3kg LPG gas.